Herpetofauna In the Ledok Ombo Natural Tourism Area, Malang District, East Java - Hanifa, Berry Fakhry; Baihaqi, Ahmad Panji; Ahmad, Mujahidin; Kiptiyah, Kiptiyah; Hasyim, Muhammad Asmuni (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2022)
The purpose of this study was to determine the diversity of herpetofauna in the Ledok Ombo Nature Tourism Area, Malang Regency. Herpetofauna specimens were collected using a Visual Encoumter Survey, Purposive Sampling at 07-11 PM. Specimens were collected 3 times one week apart in March 2022. The data was analyzed using Shannon Weiener Diversity, Pielou Evenness, Margalef Richness, and Simpson Dominance indices. Habitat Characteristic were recorded. Water-air temperature and air humidity were recorded. The results showed 9 species of amphibians (Chalcorana chalconota, Microhyla achatina, Duttaphrynus melanostictus, Phrynoidis aspera, Leptobrachium hasseltii, Odorrana hosii, Rhacoporus reinwardtii, Polypedates leucomystax, Occydozyga lima) and 9 species of reptiles (Cyrtodactylus marmoratus, Hemydactylus frenatus, Gonocephalus kuhlii, Broncochela jubata, Eutropis multifasciata, Pareas carinatus, Ahetulla prasina, Dendrelaphis pictus, Lycodon subcinctus). The index values of diversity, evenness, richness, and dominance are 1,591, 0,088, 3,250, 0,398 respectively. Habitat character affect the composition of herpetofauna. Physical factors value range for water temperature 23 - 24.55°C, air temperature 25.05 - 27.15°C, and air humidity 77.25 - 84.75%.